2002
DOI: 10.2135/cropsci2002.1173
|View full text |Cite
|
Sign up to set email alerts
|

Kernel Number Prediction in Maize under Nitrogen or Water Stress

Abstract: Final kernel number in maize (Zea mays L.) is closely associated with the physiological condition of the crop during the critical period bracketing silking. The objective of this study was to determine whether there is a common underlying relationship between kernel number per plant (KNP) and plant growth rate (PGR) during that critical period when plant growth varies because of different abiotic stresses. A relationship between KNP and PGR obtained from a previous study of variation in plant density and incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
1
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(137 citation statements)
references
References 22 publications
(41 reference statements)
8
118
1
10
Order By: Relevance
“…Kernel growth and development in corn is highly dependent on assimilate supply from concurrent photosynthesis, supplemented with remobilized stem carbohydrate reserves during grain fill [11] [12]. Although the A measurements in this study were conducted at the vegetative growth stage, we could perhaps relate the reduction in A to the reduction in grain yield at the different soil moisture treatments and growth stages.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Kernel growth and development in corn is highly dependent on assimilate supply from concurrent photosynthesis, supplemented with remobilized stem carbohydrate reserves during grain fill [11] [12]. Although the A measurements in this study were conducted at the vegetative growth stage, we could perhaps relate the reduction in A to the reduction in grain yield at the different soil moisture treatments and growth stages.…”
Section: Discussionmentioning
confidence: 96%
“…A major effect of soil moisture reduction in plants is reduction in photosynthesis [8]- [10]. Kernel growth and development in corn is highly dependent on assimilate supply from concurrent photosynthesis, supplemented with remobilized stem carbohydrate reserves during grain fill [11] [12]. Responses of photosynthesis and photosynthetic pigments content (chlorophyll and carotenoids), chlorophyll fluorescence, relative water content and other physiological parameters are often used to determine the effects of soil moisture stress in plants [13]- [15].…”
mentioning
confidence: 99%
“…It could be suggested that the high concentration of soil nitrogen contained in site A (2014) could have resulted in significantly higher assimilatory surface observed. Nitrogen deficiency had been implicated in leaf growth, activity of Ribulosebiphosphate carboxylase/oxygenase and the rate of hormone synthesis (Andrade et al, 2002;Jones and Setter, 2000). Potassium had also been implicated in reduced stalk lodging, increased stomatal conductance, increased photosynthetic capacity, protein uptake of K/NO3 ion and turgor pressure (Pettigrew, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Jumlah biji per tongkol dan bobot 1.000 biji menyebabkan perbedaan indeks toleran antar genotipe. Salah satu penyebab perbedaan hasil biji jagung yang defisiensi N, karena perbedaan jumlah biji dan bobot biji (Andrade et al, 2002;D'Andrea et al, 2008;Moser et al, 2006;Oikeh et al, 1998). Jumlah biji per tongkol yang lebih banyak pada genotipe yang sama menunjukkan penyerbukan lebih baik, sedangkan bobot biji yang lebih tinggi menunjukkan transfer hasil fotosintesis ke biji juga lebih baik.…”
Section: Hasil Dan Pembahasanunclassified